The Evolution of Morpho-Syntactic Mood in Arabic: A View from early Christian Arabic Gospel Manuscripts - Stokes, Phillip W. ca. 20./21. Jh. (Journal of Semitic studies, 2024)
Phillip W Stokes; The Evolution of Morpho-Syntactic Mood in Arabic: A View from early Christian Arabic Gospel Manuscripts, Journal of Semitic Studies, Volume 69